A mathematical model for peristaltic transport of micro-polar fluids - Pandey S.K.; Tripathi D. (My University, 2025)
A mathematical model has been constructed for peristaltic transport of micro-polar fluid in a circular cylindrical tube of finite length by letting sinusoidal waves propagate along the wall that induce contraction and relaxation but not expansion beyond the natural boundary. Axial and radial velocities and micro-rotation components are formulated for micro-polar fluid transportations by applying the method of long wavelength and low Reynolds number approximations in the analysis. Pressure distribution along the tube length is studied to investigate temporal effects. An in-depth study has been done to learn the effects of coupling number and micro-polar parameter. The effects of coupling number and micro-polar parameter are investigated also on mechanical efficiency, reflux and trapping. A significant difference observed is that unlike integral wave-trains propagating along the tube walls that have identical peaks of pressure, non-integral wave-trains have peaks of different sizes. © 2011 IOS Press and the authors. All rights reserved.